2010
DOI: 10.1161/circimaging.109.932921
|View full text |Cite
|
Sign up to set email alerts
|

Preload Dependency of Left Ventricular Torsion

Abstract: Background Left ventricular (LV) rotation results from contraction of obliquely oriented myocardial fibers. The net difference between systolic apical counterclockwise rotation and basal clockwise rotation is left ventricular torsion (LVT). Although LVT is altered in various cardiac diseases, determinants of LVT are incompletely understood. Methods and Results LV end-diastolic volume (LVEDV), LV apical and basal rotation, peak systolic LVT, and peak early diastolic untwisting rate (UTR) were measured by spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
77
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 35 publications
6
77
4
Order By: Relevance
“…Contrary to this hypothesis, early diastolic filling was not improved beyond normothermic baseline, possibly explained by the reduction in LV torsion, twisting rate, and untwisting rate during HDT heat stress, which appeared to be preload dependent. This result is in direct contrast with a recent report (33) that found that increasing preload (saline infusion) augmented peak systolic LV torsion and peak early diastolic untwisting rate. Two important differences exist between the present investigation and the aforementioned study (33), however, which likely contributes to this discrepancy.…”
Section: Diastolic Functioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to this hypothesis, early diastolic filling was not improved beyond normothermic baseline, possibly explained by the reduction in LV torsion, twisting rate, and untwisting rate during HDT heat stress, which appeared to be preload dependent. This result is in direct contrast with a recent report (33) that found that increasing preload (saline infusion) augmented peak systolic LV torsion and peak early diastolic untwisting rate. Two important differences exist between the present investigation and the aforementioned study (33), however, which likely contributes to this discrepancy.…”
Section: Diastolic Functioncontrasting
confidence: 99%
“…This result is in direct contrast with a recent report (33) that found that increasing preload (saline infusion) augmented peak systolic LV torsion and peak early diastolic untwisting rate. Two important differences exist between the present investigation and the aforementioned study (33), however, which likely contributes to this discrepancy. First, supine heat stress significantly alters heart rate, afterload [LV endsystolic wall stress (17)], preload, and contractility, whereas saline infusion appeared only to alter preload and systolic function (longitudinal, circumferential, and radial strain).…”
Section: Diastolic Functioncontrasting
confidence: 99%
“…31 In a human study, investigators have demonstrated increased isovolumic untwist rate after increased preload. 32 In our study we also find larger LV volumes along with elevated s and LV minimum diastolic pressure in LVDD, suggesting that LV preload may be playing a role in increased untwist rate. On the other hand, no relationship between Àdφ 0 /dV 0 and LV volumetric or structural characteristics was found.…”
Section: Discussionsupporting
confidence: 73%
“…Some previous reports indicate that systolic twisting is preload dependent, 5,8,9 whereas others have reported only a minor preload dependence or none at all. 10,11 We hypothesized that diastolic pressure has a direct effect on UTR similar to the effect of early-diastolic load on LV lengthening rate.…”
mentioning
confidence: 92%
“…1,3,6,7 It is not clear, however, whether LV relaxation and restoring forces are independent determinants of UTR. Furthermore, a recent study 8 showed increased UTR during volume loading, which tends to increase (slower relaxation) and ESV (decreased restoring forces), as well. Increased UTR despite slowed relaxation and reduced restoring forces suggests that UTR is not solely determined by these 2 factors.…”
mentioning
confidence: 95%